Effects of Half-Time Cooling Using a Fan with Skin Wetting on Thermal Response During Intermittent Cycling Exercise in the Heat - Osakabe, Jumpei; Kajiki, Masanobu; Kondo, Kiho; Matsumoto, Takaaki; Umemura, Yoshihisa (Sports Medicine International Open, 2021)
The present study investigated the effects of half-time (HT) break cooling using a fan and damp sponge on physiological and perceptual responses during the 2nd half of a repeated-sprint exercise in a hot environment. Eight physically active men performed a familiarization trial and two experimental trials of a 2×30-min intermittent cycling exercise protocol with a 15-min HT break in hot conditions (35°C, 50% relative humidity). Two experimental trials were conducted in random order: skin wetting with a fan (FANwet) and no cooling (CON). During the 2nd half, a repeated-sprint cycling exercise was performed: i. e., 5 s of maximal pedaling (body weight×0.075 kp) every minute, separated by 25 s of unloaded pedaling (80 rpm) and 30 s of rest. Rectal temperature, skin temperature (chest, forearm, thigh, and calf), heart rate, physiological strain index, rating of perceived exertion, thermal sensation, and comfort were significantly improved in the FANwet condition (P<0.05). There was no significant difference in the repeated-sprint cycling exercise performance between conditions. The results suggest that skin wetting with a fan during the HT break is a practical and effective cooling strategy for mitigating physiological and perceptual strain during the 2nd half in hot conditions.
Keywords: evaporative heat loss; core temperature; thermal sensation; thermal stress